Determination of the seismic performance of a historical masonry structure using the equivalent seismic load method - Yetkın, Musa; Erkek, Hakan; Dedeoğlu, İbrahim Özgür; Calayır, Yusuf (My University, 2023)
Mosques and masjids are the most important parts of Islamic culture in terms of their architectural and structural characteristics. These structures also provide an important insight into the construction techniques and historical process of the region in which they were built. Many of these structures are still in use around the world. However, most historical mosques and masjids are vulnerable to earthquakes or are not strong enough. Therefore, it is important to know the risk status of these important structures with respect to earthquake forces and to carry out the necessary strengthening works. In this study, the performance of the historical Ahi Musa Masjid (built in 1185) was investigated using the linear earthquake solution method, which provides a practical approach to determining the earthquake performance of historical structures. Firstly, studies were carried out to determine the geometric and material properties of the historical Masjid. A finite element model of the historical Masjid was then constructed and linear performance analyses were performed under vertical loads and equivalent earthquake loads. As a result of the analyses, the displacement ratios, compressive and shear stresses of the historical Masjid were obtained and evaluated according to the collapse prevention performance level for the earthquake level DD-3, which is one of the performance levels recommended for historical structures of local importance in the Guidelines for the Management of Earthquake Risks for Historical Structures. The aforementioned stress and drift ratio values remained below the reference values. In conclusion, the Masjid will safely withstand the potential effects of an earthquake.
Keywords: Finite element model; Seismic performance; Historical masjid; Masonry structures; Equivalent earthquake load method